Rodząca się czeska tożsamość narodowa a męska pozycja społeczna - Filipowicz, Marcin (Slavia Occidentalis, 2013)
The article focuses on the issue of the relationship between emerging Czech national identity and male social leadership in the 19th century. The article deals with the question of male social representation related to prestige that Czech literary discourse tried to elaborate. The article concerns the attitude towards hegemonic masculinity linked to Austrian structures of power and of Germanic culture. This issue has been explored on the example of prose created by male authors originating in the period of increased national agitation which lasted from approximately the 1830s to the end of the 1870s. Focusing on reconstructions of collective normative imaginations based on literary texts is, however, insufficient. There is agreement, but also the difference between imaginatinggs, and their implementation. Therefore, literary patterns related to the social position of the Czech male patriot were confronted with the image of their “reality” preserved in Czech memoirs of the 19th century.